Electroreceptor neuron dynamics shape information transmission - Chacron, Maurice J (Nat Neurosci, 2005)
The gymnotiform weakly electric fish Apteronotus leptorhynchus can capture prey using electrosensory cues that are dominated by low temporal frequencies. However, conventional tuning curves predict poor electroreceptor afferent responses to low-frequency stimuli. We compared conventional tuning curves with information tuning curves and found that the latter predicted substantially improved responses to these behaviorally relevant stimuli. Analysis of receptor afferent baseline activity showed that negative correlations reduced low-frequency noise levels, thereby increasing information transmission. Multiunit recordings from receptor afferents showed that this increased information transmission could persist at the population level. Finally, we verified that this increased low-frequency information is preserved in the spike trains of central neurons that receive receptor afferent input. Our results demonstrate that conventional tuning curves can be misleading when certain noise reduction strategies are used by the nervous system.